Laminate and method for producing same

The laminate structure with metal-coated resin particles and low-melting-point metal particles addresses the challenge of achieving high thermal conductivity in thermal conductive materials, enhancing flexibility and processability, particularly with silicon-based heat generating elements.

CN119156282AActive Publication Date: 2024-12-17DEXERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380037590.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-05-25
Publication Date
2024-12-17
Estimated Expiration
2043-05-25

AI Technical Summary

Technical Problem

Existing thermal conductive materials face challenges in achieving high thermal conductivity, particularly when used with silicon or similar heat generating elements, and often suffer from poor processability, weight, and flexibility issues.

Method used

A laminate structure comprising a substrate with metal-coated resin particles arranged at predetermined intervals, a curing component, a curing agent, thermally conductive particles, and low-melting-point metal particles, where the volume average particle size of the metal-coated resin particles is smaller than the thermally conductive particles, forming a network for enhanced thermal conductivity.

Benefits of technology

The laminate achieves high thermal conductivity by increasing the contact area and forming a network of low-melting-point metal particles, improving thermal conductivity even with substrates like silicon, while maintaining flexibility and processability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156282A_ABST
    Figure CN119156282A_ABST
Patent Text Reader

Abstract

Provided is a laminate having a base material, and a heat-conducting layer which contains a curing component, a curing agent for curing the curing component, heat-conducting particles, and low-melting-point metal particles, the heat-conducting layer containing metal-coated resin particles on the base material in a state in which the metal-coated resin particles are separated and arranged at predetermined intervals, and the heat-conducting layer containing the curing component, the curing agent, the heat-conducting particles, and the low-melting-point metal particles. The metal-coated resin particles are in contact with the base material, the volume average particle diameter of the metal-coated resin particles is smaller than the volume average particle diameter of the thermally conductive particles, and the base material contains at least one selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate and a method for producing the laminate. Background Art

[0002] In LSI (Large Scale Integration) and other electronic devices, if the LSI itself is exposed to high temperature for a long time due to the heat generated by the components used, there is a concern that it may cause malfunction and failure. Therefore, in order to prevent the temperature rise of LSI and the like, thermal conductive materials are widely used. The thermal conductive materials can prevent the temperature rise of the device by diffusing or conducting the heat generated by the components to a heat dissipation component for discharging to the outside of the system such as the atmosphere.

[0003] If metal or ceramic is used as such a heat conducting material, it is difficult to reduce weight, has poor processability, or has low flexibility. Therefore, various heat conducting materials using polymer materials formed of resin, rubber, etc. as a base material have been proposed.

[0004] For example, a thermally conductive adhesive has been proposed, which includes a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, the metal filler including silver powder and solder powder, the solder powder exhibiting a melting temperature lower than the thermal curing treatment temperature of the thermally conductive adhesive and reacting with the silver powder under the thermal curing treatment conditions of the thermosetting adhesive to generate a high melting point solder alloy exhibiting a melting point higher than the melting temperature of the solder powder, the curing agent being a curing agent having flux activity for the metal filler, the curing component being a glycidyl ether type epoxy resin, and the curing agent being a monoanhydride of a tricarboxylic acid (for example, refer to Patent Document 1).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 5796242 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, in the prior art described in Patent Document 1, the heat dissipation module in the heat dissipation structure can achieve high thermal conductivity through metal bonding. However, the heat generating elements (electronic components) in the heat dissipation structure are often made of silicon or the like, and there is a problem that it is difficult to achieve high thermal conductivity by metal bonding.

[0010] The present invention aims to solve the above-mentioned problems in the related art and to achieve the following objectives: That is, the present invention aims to provide a laminate and a method for producing the laminate that can achieve high thermal conductivity.

[0011] Methods used to solve problems

[0012] The method for solving the above-mentioned problem is as follows.

[0013] <1> A laminate comprising: a substrate, and

[0014] On the substrate, the metal-coated resin particles are arranged in a state of being separated at predetermined intervals, and the heat-conductive layer contains a curing component, a curing agent for curing the curing component, heat-conductive particles, and low-melting-point metal particles,

[0015] The metal-coated resin particles are in contact with the substrate, the volume average particle size of the metal-coated resin particles is smaller than the volume average particle size of the thermally conductive particles,

[0016] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.

[0017] <2> The laminated body according to <1> above, wherein the metal-coated resin particles are in contact with a portion of the thermally conductive particles included in the thermally conductive layer.

[0018] <3> The laminate according to <1> or <2>, wherein a ratio (A:B) of a volume average particle size A of the metal-coated resin particles to a volume average particle size B of the thermally conductive particles is 1:2 to 1:20.

[0019] <4> The laminate according to any one of <1> to <3>, wherein the metal-coated resin particles have a volume average particle size of 0.3 μm or more and 30 μm or less.

[0020] <5> The laminated body according to any one of <1> to <4>, wherein the thermally conductive particles have a volume average particle size of 1 μm to 100 μm.

[0021] <6> The laminate according to any one of <1> to <5>, wherein the metal-coated resin particles are at least one selected from the group consisting of gold-plated resin particles, silver-plated resin particles, copper-plated resin particles, and nickel-plated resin particles.

[0022] <7> The laminated body according to any one of <1> to <6>, wherein the thermally conductive particles are at least any one of copper particles, silver-coated particles, and silver particles.

[0023] <8> The laminate according to any one of <1> to <7>, wherein the low-melting-point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In.

[0024] <9> The laminate according to any one of <1> to <8>, wherein the curing component is at least one of an oxirane ring compound and an oxetane compound.

[0025] <10> The laminate according to any one of <1> to <9>, comprising an opposing substrate on the thermally conductive layer that is opposed to the substrate,

[0026] The opposing substrate includes at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.

[0027] <11> A method for producing a laminate, characterized in that it comprises the following steps:

[0028] A heat conductive layer forming step of forming a heat conductive layer on a substrate, wherein the heat conductive layer includes metal coated resin particles arranged at predetermined intervals and containing a curing component, a curing agent for curing the curing component, heat conductive particles, and low melting point metal particles.

[0029] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.

[0030] Effects of the Invention

[0031] According to the present invention, the above-mentioned various problems of the related art can be solved, the above-mentioned objects can be achieved, and a laminated body and a method for producing the laminated body that can realize high thermal conductivity can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1A It is a schematic diagram showing an example of the laminated body before compression bonding according to the first embodiment.

[0033] Figure 1B It is a schematic diagram showing an example of the laminated body after compression bonding according to the first embodiment.

[0034] Figure 2 This is a schematic cross-sectional view showing an example of a heat dissipation structure used in the present invention.

[0035] Figure 3 This is a SEM photograph of a cross section of the laminate of Example 4 at a position where the thermal conductive layer and the substrate are in contact. DETAILED DESCRIPTION

[0036] (Laminated body)

[0037] The laminate of the present invention comprises a substrate and a heat conductive layer containing metal-coated resin particles arranged and spaced at predetermined intervals, preferably an opposing substrate, and further comprises other members as required.

[0038] In the present invention, a thermally conductive layer is provided on a substrate in which metal-coated resin particles are arranged and separated at predetermined intervals. The metal-coated resin particles are in contact with the substrate. The volume average particle size of the metal-coated resin particles is smaller than the volume average particle size of the thermally conductive particles. The contact area is increased due to deformation of the metal-coated resin particles. Thus, even if the substrate is made of at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel and ceramics and has poor solder wettability, the thermal conductivity can be greatly improved.

[0039] <Base material>

[0040] The shape, structure, size, material, etc. of the substrate are not particularly limited and can be appropriately selected depending on the purpose.

[0041] Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the intended use, etc.

[0042] The material of the substrate is a material that is not easily wetted by solder, and includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, aluminum oxide, gallium nitride, etc. Examples of the molding resin include epoxy resin, silicone resin, urethane resin, acrylic resin, etc.

[0043] The average thickness of the substrate is not particularly limited and can be appropriately selected depending on the intended purpose.

[0044] The substrate may be the heat generating element (electronic component) itself in the heat dissipating structure.

[0045] <Thermal Conductive Layer>

[0046] The thermally conductive layer contains metal-coated resin particles arranged and spaced at predetermined intervals, and includes a curing component, a curing agent for curing the curing component, thermally conductive particles, and low-melting-point metal particles, and further contains other components as necessary.

[0047] -Curing ingredients-

[0048] As the curing component, it is preferred to use at least one of an oxirane ring compound and an oxetane compound.

[0049] --Oxirane ring compounds--

[0050] The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resins.

[0051] As the above-mentioned epoxy resin, there is no particular restriction, and it can be appropriately selected according to the purpose, and for example, glycidyl ether type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type epoxy resin, trisphenol type epoxy resin, tetraphenol type epoxy resin, phenol-xylylene type epoxy resin, naphthol-xylylene type epoxy resin, phenol-naphthol type epoxy resin, phenol-dicyclopentadiene type epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, etc. can be mentioned. They can be used alone or in combination of two or more.

[0052] --Oxetane compounds--

[0053] The oxetane compound is a compound having an oxetane group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound.

[0054] The oxetane compound may be a monofunctional oxetane compound having only one oxetane group, or may be a polyfunctional oxetane compound having two or more oxetane groups.

[0055] The oxetane compound is not particularly limited and can be appropriately selected according to the purpose. For example, 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmethyl)ether, -3-oxetanylmethoxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), etc. These may be used alone or in combination of two or more.

[0056] As the oxetane compound, a commercially available product can be used, and examples of the commercially available product include “ARONE OXETANE (registered trademark)” series sold by Toagosei Co., Ltd. and “ETERNACOLL (registered trademark)” series sold by Ube Industries, Ltd.

[0057] Among the above-mentioned oxirane ring compounds and oxetane compounds, preferred are glycidyl ether epoxy resins, phenol novolac epoxy resins, cresol novolac epoxy resins, phenol-dicyclopentadiene epoxy resins, bisphenol A epoxy resins, aliphatic epoxy resins, and 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP).

[0058] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5 mass % to 60 mass % based on the total amount of the first heat conductive layer.

[0059] -Curing agent-

[0060] As the above-mentioned curing agent, it is a curing agent corresponding to the above-mentioned curing component, for example, anhydride curing agents, aliphatic amine curing agents, aromatic amine curing agents, phenol curing agents, thiol curing agents and other addition-type curing agents, catalyst-type curing agents such as imidazoles, etc. can be cited. They can be used alone or in combination of two or more. Among these, anhydride curing agents are preferably used. When the curing component of the above-mentioned anhydride curing agent is an epoxy resin, there is no generation of gas during heat curing, and a long storage period can be achieved when mixed with the epoxy resin. In addition, it is preferred from the perspective of being able to achieve a good balance between the electrical properties, chemical properties and mechanical properties of the resulting cured product.

[0061] Examples of the acid anhydride curing agent include cyclohexane-1,2-dicarboxylic anhydride and tricarboxylic acid monoanhydride. Examples of the tricarboxylic acid monoanhydride include cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride.

[0062] The curing agent has flux activity, which is preferred from the perspective of improving the wettability of the molten low-melting-point metal particles relative to the thermally conductive particles. As a method for the curing agent to exhibit flux activity, for example, a method of introducing a protonic acid group such as a carboxyl group, a sulfonyl group, or a phosphate group into the curing agent using a known method can be cited. Among these, from the perspective of reactivity with an epoxy resin or an oxetane compound as a curing component, it is preferred to introduce a carboxyl group, and for example, organic acids containing carboxyl groups such as glutaric acid and succinic acid can be cited. In addition, it can be a compound modified by glutaric anhydride or succinic anhydride or a metal salt of an organic acid such as silver glutarate.

[0063] The content of the curing agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1% by mass or more and 30% by mass or less based on the total amount of the heat conductive layer.

[0064] The equivalent ratio (C / D) of the curing component C and the curing agent D on a molar equivalent basis varies depending on the types of the curing component and curing agent used, and cannot be generally specified, but is preferably 0.5 to 3, more preferably 0.5 to 2, and further preferably 0.7 to 1.5. When the equivalent ratio (C / D) is 0.5 to 3, there is an advantage that when the thermal conductive composition is thermally cured, the low melting point metal particles are sufficiently melted to form a network.

[0065] -Thermal Conductive Particles-

[0066] As the thermally conductive particles, at least any one of copper particles, silver-coated particles, and silver particles is preferred.

[0067] Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.

[0068] The shape of the thermally conductive particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples of the shape include spherical, flat, granular, and needle-like particles.

[0069] The volume average particle size of the thermally conductive particles is preferably 1 μm to 100 μm, more preferably 10 μm to 70 μm, and further preferably 10 μm to 50 μm. If the volume average particle size of the thermally conductive particles is 1 μm to 100 μm, the volume ratio of the thermally conductive particles to the low melting point metal particles can be increased, and high thermal conductivity can be achieved. The volume average particle size can be measured, for example, by laser diffraction and a scattered particle size distribution measuring device (product name: Microtrac MT3300EXII).

[0070] -Low melting point metal particles-

[0071] As the low melting point metal particles, solder particles specified in JIS Z3282-1999 are preferably used.

[0072] As the above-mentioned solder particles, for example, Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. can be cited. They can be used alone or in combination of two or more. Among these, preferably, a solder particle containing Sn and at least one selected from Bi, Ag, Cu and In is used, and more preferably, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Ag-Cu solder particles, and Sn-In solder particles are used.

[0073] The shape of the low melting point metal particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples of the shape include spherical, flat, granular, and needle-like particles.

[0074] The melting point of the low-melting-point metal particles is preferably 100°C to 250°C, and more preferably 120°C to 200°C.

[0075] The melting point of the low melting point metal particles is lower than the heat curing temperature of the thermally conductive composition, and it is preferred that the low melting point metal particles are melted in the cured thermally conductive composition to form a network (continuous phase of metal) through the thermally conductive particles, thereby achieving high thermal conductivity.

[0076] The low melting point metal particles react with the thermally conductive particles under the heat curing conditions of the thermally conductive composition to form an alloy having a higher melting point than the low melting point metal particles, thereby preventing melting at high temperatures and improving reliability. In addition, the heat resistance of the cured thermally conductive composition is improved.

[0077] The heat curing treatment of the thermally conductive composition is performed, for example, at a temperature of 150° C. to 200° C. for 30 minutes to 2 hours.

[0078] The volume average particle size of the low melting point metal particles is preferably 10 μm or less, more preferably 1 μm or more and 5 μm or less. If the volume average particle size of the low melting point metal particles is 10 μm or less, the volume ratio of the low melting point metal particles to the thermally conductive particles can be reduced, and high thermal conductivity can be achieved.

[0079] The volume average particle size of the low melting point metal particles can be measured in the same manner as the volume average particle size of the thermally conductive particles.

[0080] The volume average particle size of the thermally conductive particles is larger than the volume average particle size of the low melting point metal particles, and the volume average particle size ratio (A / B) of the thermally conductive particles A to the low melting point metal particles B is preferably 2 or more, more preferably 3 or more, and further preferably 5 or more. The upper limit of the volume average particle size ratio (A / B) is preferably 20 or less, and more preferably 10 or less.

[0081] By using low-melting-point metal particles having a smaller volume average particle size than the thermally conductive particles, the thermally conductive particles become the main component in the thermally conductive composition, and the low-melting-point metal particles between the thermally conductive particles are melted by heating and alloyed with the thermally conductive particles to form a network, thereby achieving high thermal conductivity.

[0082] The volume ratio (A / B) of the thermally conductive particles A to the low-melting-point metal particles B in the thermally conductive layer is preferably 1 or more, more preferably 1.5 or more, and further preferably 2 or more. The upper limit of the above-mentioned volume ratio (A / B) is preferably 5 or less, more preferably 4 or less, and further preferably 3 or less. If the above-mentioned volume ratio (A / B) is 1 or more, the volume proportion of the thermally conductive particles having a larger volume average particle size than the low-melting-point metal particles increases, thereby suppressing the flow of the molten low-melting-point metal particles. In addition, the low-melting-point metal particles are not easy to separate even for interfaces that are not easily wetted (for example, aluminum), so the influence of the material of the interface can be suppressed, and the selectivity of the interface material is improved.

[0083] -polymer-

[0084] The heat conductive layer preferably contains a polymer in order to impart flexibility and the like.

[0085] The polymer is not particularly limited and can be appropriately selected according to the purpose. Examples thereof include polymers having at least one structure selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure in the molecule.

[0086] The content of the polymer is preferably 1 mass % to 50 mass % based on the total amount of the heat conductive layer, more preferably 1 mass % to 30 mass %, and even more preferably 1 mass % to 10 mass %.

[0087] -Other ingredients-

[0088] The above-mentioned heat-conducting layer may contain other components as long as the effect of the present invention is not impaired. There are no particular restrictions on the above-mentioned other components, and they can be appropriately selected according to the purpose, and examples thereof include heat-conducting particles other than metals (for example, aluminum nitride, aluminum oxide, carbon fiber, etc.), additives (for example, antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.), etc.

[0089] In the present invention, the heat conductive layer is formed by arranging the metal coated resin particles at predetermined intervals. That is, the heat conductive layer has a particle arrangement layer on the surface in contact with the substrate.

[0090] The metal-coated resin particles are in contact with the substrate, and preferably the metal-coated resin particles are in contact with a portion of the thermally conductive particles included in the thermally conductive layer. Thus, high thermal conductivity can be achieved.

[0091] The state where the metal-coated resin particles are arranged at predetermined intervals on the surface of the side of the thermal conductive layer in contact with the substrate is included, and when the substrate is transparent to visible light such as glass, it can be easily confirmed using an optical microscope, etc. In addition, when the substrate is transparent to infrared light such as silicon, it can be observed using an infrared microscope. In addition, when the substrate is a molding resin or ceramics, it can be observed using an X-ray microscope.

[0092] -Metal-coated resin particles-

[0093] As the metal coated resin particles, preferably resin particles with high thermal conductivity and relatively softness, for example, gold-plated resin particles, silver-plated resin particles, copper-plated resin particles, nickel-plated resin particles, etc. can be mentioned. These can be used alone or in combination of two or more. Among these, gold-plated resin particles are preferred from the perspective of thermal conductivity and stability.

[0094] Examples of the material of the resin particles include divinylbenzene polymers, polystyrene resins, epoxy resins, phenolic resins, acrylic resins, acrylonitrile-styrene (AS) resins, and benzoguanamine resins, etc. These may be used alone or in combination of two or more.

[0095] The volume average particle size of the metal-coated resin particles is preferably 0.3 μm or more and 30 μm or less, and more preferably 0.5 μm or more and 10 μm or less.

[0096] The volume average particle size of the metal-coated resin particles can be measured in the same manner as the volume average particle size of the thermally conductive particles.

[0097] The metal-coated resin particles are preferably exposed at least partially from the thermally conductive layer, so that when the laminate is pressed, the metal-coated resin particles deform and the binder component melts and reaches the substrate surface, thereby improving adhesion to the thermally conductive layer.

[0098] The metal-coated resin particles are preferably arranged in a regular manner with a predetermined arrangement repeated when viewed from above the thermally conductive layer. The arrangement of the metal-coated resin particles can be, for example, a square lattice arrangement when viewed from above the thermally conductive layer. In addition, as a regular arrangement of the metal-coated resin particles, lattice arrangements such as a rectangular lattice, an oblique lattice, a hexagonal lattice, a triangular lattice, etc. can be cited. In the arrangement of the metal-coated resin particles, lattices of different shapes can be combined in multiples. As a method of arranging the metal-coated resin particles, the metal-coated resin particles can arrange the particle columns arranged linearly at predetermined intervals in parallel at predetermined intervals. The areas where the metal-coated resin particles are densely arranged and the areas where the metal-coated resin particles are sparsely arranged can be regularly repeated. It is preferred that the metal-coated resin particles are independently separated from each other from the perspective of improving thermal conductivity. In addition, a plurality of metal-coated resin particles are connected or close to form a unit, and the method of regularly arranging the unit is also included.

[0099] When the metal-coated resin particles are regularly arranged, the lattice axis or arrangement axis of the arrangement may be parallel to or intersect at least one of the longitudinal direction of the heat conductive layer and a direction perpendicular to the longitudinal direction.

[0100] The distance between the particles of the metal-coated resin particles is not particularly limited and can be appropriately selected according to the purpose. For example, the distance between the closest particles is preferably 0.5 times or more of the volume average particle size of the metal-coated resin particles, and more preferably 0.7 times or more. On the other hand, the distance between the closest particles is preferably 100 times or less of the volume average particle size of the metal-coated resin particles, and more preferably 50 times or less.

[0101] The number density of the metal-coated resin particles is preferably 100 particles / mm 2 More than 300 pieces / mm 2 More than 70,000 pieces / mm 2 Below, more preferably 6,000 pieces / mm 2 Above 45,000 pieces / mm 2 the following.

[0102] The average thickness of the heat conductive layer is not particularly limited and can be appropriately selected depending on the intended purpose, but is preferably 0.1 μm to 100 μm, and more preferably 1 μm to 30 μm.

[0103] <Opposing substrate>

[0104] The opposing substrate is disposed to face the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose.

[0105] Examples of the shape of the opposing substrate include a plate shape, a sheet shape, etc. Examples of the structure of the opposing substrate include a single layer structure, a laminated structure, etc. The size of the opposing substrate can be appropriately selected according to the intended use, etc.

[0106] The material of the opposing substrate is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.

[0107] The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the intended purpose.

[0108] The opposing substrate may be the heat dissipation module itself in the heat dissipation structure.

[0109] <Other components>

[0110] The other member is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include an intermediate layer and a protective layer.

[0111] (Method for producing laminated body)

[0112] The method for producing a laminated body of the present invention includes a heat conductive layer forming step and further includes other steps as necessary.

[0113] <Heat conduction layer forming step>

[0114] The thermally conductive layer forming step is a step of forming a thermally conductive layer on a substrate, which contains metal-coated resin particles arranged at predetermined intervals and includes a curing component, a curing agent for curing the curing component, thermally conductive particles, and low-melting-point metal particles.

[0115] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.

[0116] The metal-coated resin particles are the same as the metal-coated resin particles included in the thermally conductive layer, and the description thereof is omitted. In addition, the curing component, the curing agent, the first thermally conductive particles, and the low-melting-point metal particles are the same as the curing component, the curing agent, the first thermally conductive particles, and the low-melting-point metal particles included in the thermally conductive layer, and the description thereof is omitted.

[0117] As a method for forming a thermally conductive layer containing the above-mentioned metal-coated resin particles separated and arranged at predetermined intervals, for example, a mold having a concave portion corresponding to the arrangement pattern of the metal-coated resin particles is prepared, the metal-coated resin particles are filled in the concave portion of the mold, and a thermally conductive layer containing a curing component, a curing agent for curing the curing component, thermally conductive particles, and low-melting-point metal particles formed on a release film is laminated thereon to press the metal-coated resin particles. Thus, by rotating the metal-coated resin particles in a predetermined pattern on the thermally conductive layer, a thermally conductive film in which the metal-coated resin particles are separated and arranged at predetermined intervals can be formed. The thermally conductive film can be made into a thermally conductive film having a two-layer structure in which an insulating adhesive layer is supported by laminating a release film to the metal-coated resin particle arrangement layer as needed.

[0118] By placing the thermally conductive film on the substrate so that the metal-coated resin particles are in contact with each other and then pressing them, a thermally conductive layer including the metal-coated resin particles arranged at predetermined intervals can be formed.

[0119] The thermally conductive film can be produced, for example, by applying a thermally conductive composition containing a curing component, a curing agent for curing the curing component, thermally conductive particles, and low-melting-point metal particles to a release film and curing the composition.

[0120] Examples of a method for applying the thermally conductive composition to the release film include an inkjet method, a doctor blade coating method, a gravure coating method, a gravure offset coating method, a rod coating method, a roll coating method, a knife coating method, an air knife coating method, a comma coating method, a U-comma coating method, an AKKU coating method, a smooth coating method, a micro gravure coating method, a reverse roll coating method, a four-roll coating method, a five-roll coating method, a dip coating method, a curtain coating method, a slide coating method, and a die coating method.

[0121] <Other Process>

[0122] The other steps are not particularly limited and can be appropriately selected depending on the purpose.

[0123] Here, about the embodiment of the laminated body of the present invention, it is described in detail with reference to the accompanying drawings. In addition, in each accompanying drawing, the same component is attached with the same symbol, and repeated description is sometimes omitted. In addition, the number, position, shape, etc. of the following constituent members are not limited to the form of this implementation, and on the basis of implementing the present invention, it can become a preferred number, position, shape, etc.

[0124] <First embodiment>

[0125] Figure 1AThe schematic diagram shows an example of a laminated body before lamination according to the first embodiment. The laminated body 10 of FIG1 has a thermally conductive layer 13 on a substrate 11, which contains metal-coated resin particles 15 arranged at predetermined intervals, and contains a curing component, a curing agent for curing the curing component, thermally conductive particles, and low-melting-point metal particles, and has an opposing substrate 14 on the thermally conductive layer 13.

[0126] The metal-coated resin particles 15 are in contact with the substrate 11 , and the volume average particle size of the metal-coated resin particles is smaller than the volume average particle size of the thermally conductive particles. The metal-coated resin particles 15 are preferably at least partially exposed from the thermally conductive layer 13 .

[0127] Figure 1B This is a schematic diagram showing an example of the laminate before pressing according to the first embodiment. When the laminate is pressed, the metal coated resin particles 15 are deformed and the binder component in the thermal conductive layer melts and reaches the substrate surface, thereby improving the adhesion between the substrate 15 and the thermal conductive layer 13.

[0128] For example, the laminate of the present invention can be suitably used to form a power LED module or a power IC module by filling the tiny gap between a heat source such as an LSI and a heat sink, thereby connecting a heat dissipating substrate mounted with a thermal interface material (TIM) that allows heat to flow smoothly between the two, an LED chip or an IC chip, and a heat sink.

[0129] Here, as the power LED module, there are a module of a wire bonding mounting type and a module of a flip chip mounting type, and as the power IC module, there is a module of a wire bonding mounting type.

[0130] The heat dissipation structure used in the present invention is composed of a heat generating body, the laminated body of the present invention, and a heat dissipation member.

[0131] The heat generating element is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include electronic components such as a CPU (Central Processing Unit), an MPU (Micro Processing Unit), and a GPU (Graphics Processing Unit).

[0132] The heat dissipating member is not particularly limited as long as it is a structure that dissipates heat generated by an electronic component (heat generating element), and can be appropriately selected depending on the purpose. Examples thereof include heat dissipating modules, heat sinks, temperature equalizing plates, and heat pipes.

[0133] The heat dissipation module is a member for efficiently conducting the heat of the electronic component to other components. The material of the heat dissipation module is not particularly limited and can be appropriately selected according to the purpose, for example, copper, aluminum, etc. The heat dissipation module is usually in a flat plate shape.

[0134] The heat sink is a member for releasing the heat of the electronic component into the air. There is no particular limitation on the material of the heat sink, and it can be appropriately selected according to the purpose, and examples thereof include copper, aluminum, etc. The heat sink, for example, has a plurality of fins. The heat sink, for example, has a base, and a plurality of fins arranged so as to extend in a non-parallel direction (for example, an orthogonal direction) relative to one surface of the base.

[0135] Generally speaking, the heat dissipation module and the heat dissipation fin are solid structures without any space inside.

[0136] The temperature equalizing plate is a hollow structure. A volatile liquid is sealed in the inner space of the hollow structure. Examples of the temperature equalizing plate include a temperature equalizing plate having a hollow structure in the heat dissipation module and a hollow structure in the plate shape such as the heat sink.

[0137] The heat pipe is a hollow structure in a cylindrical, substantially cylindrical or flat cylindrical shape, and a volatile liquid is sealed in the inner space of the hollow structure.

[0138] here, Figure 2 FIG. 1 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates the heat generated by the electronic components 3 such as semiconductor components. Figure 2 As shown, the main surface 2a fixed to the heat dissipation module 2 and facing the electronic component 3 is sandwiched between the electronic component 3 and the heat dissipation module 2. In addition, the thermally conductive sheet 1 is sandwiched between the heat dissipation module 2 and the heat dissipation sheet 5.

[0139] The heat dissipation module 2 is formed in a square plate shape, for example, and has a main surface 2a facing the electronic component 3, and a side wall 2b erected along the outer periphery of the main surface 2a. The heat dissipation module 2 is provided with a heat conductive sheet 1 on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 is provided on the other surface 2c on the opposite side of the main surface 2a through the heat conductive sheet 1. The higher the thermal conductivity of the heat dissipation module 2, the lower the thermal resistance, and the heat of the electronic component 3 such as the semiconductor component is efficiently absorbed. For example, it can be formed using copper or aluminum with good thermal conductivity.

[0140] Electronic component 3 is, for example, a semiconductor component such as BGA, and is mounted on wiring board 6. In heat dissipation module 2, the front end surface of side wall 2b is mounted on wiring board 6, thereby surrounding electronic component 3 at a predetermined distance via side wall 2b.

[0141] Furthermore, by providing the laminated body 7 of the present invention on the main surface 2 a of the heat dissipation module 2 , heat generated by the electronic component 3 is absorbed, and a heat dissipation member is formed that dissipates the heat through the heat sink 5 .

[0142] Example

[0143] Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples.

[0144] (Example 1)

[0145] <Preparation of thermally conductive composition>

[0146] The composition and content described in Example 1 in Table 1 were uniformly mixed using a stirring device (Rentaro Automatic Revolution Mixer, manufactured by THINKY Co., Ltd.) to prepare a thermally conductive composition of Example 1. The content of each component in Table 1 is parts by mass.

[0147] <Production of thermal conductive film>

[0148] The thermally conductive composition of Example 1 was applied to a release film (PET38GS, manufactured by Lintec Corporation) by a bar coating method, heated at 80° C. for 15 minutes, and dried to prepare a thermally conductive film having an average thickness of 100 μm.

[0149] <Preparation of a film-shaped master mold with arrayed metal-coated resin particles>

[0150] First, the master mold used in the embodiment was prepared as follows. A nickel plate with a thickness of 2 mm was prepared, and a hexagonal grid pattern and cylindrical protrusions (outer diameter 4 μm, height 4 μm, center-to-center distance 6 μm) were formed in the 50 cm square area, and the surface density of the protrusions was made to be 32,000 pieces / mm 2 The transfer body master mold.

[0151] Next, a polyethylene terephthalate (PET) substrate film having a width of 50 cm and a thickness of 50 μm was prepared, and a photocurable resin composition containing 100 parts by weight of an acrylate resin (M208, manufactured by Toagosei Co., Ltd.) and 2 parts by weight of a photopolymerization initiator (IRGACURE 184, manufactured by BASF Japan Ltd.) was applied onto the PET substrate film so that the film thickness became 30 μm.

[0152] The obtained photocurable resin composition film was pressed against a nickel transfer master mold from its convex surface and heated by a high-pressure mercury lamp (1,000 mJ / cm 2), and irradiated with light from the PET substrate film side, thereby forming a photocurable resin layer in which the convex parts of the transfer master mold are transferred as concave parts. This operation is continuously repeated while aligning along the length direction of the PET substrate film, thereby obtaining a film-like master mold of about 10 m in which the convex parts of the transfer master mold are transferred as concave parts. In the obtained film-like master mold, the concave parts corresponding to the convex part pattern of the transfer master mold are arranged in a hexagonal lattice.

[0153] Next, gold-plated resin particles 1 (manufactured by Sekisui Chemical Co., Ltd., AUL703, volume average particle size 3 μm) are prepared as metal-coated resin particles, and the gold-plated resin particles are spread multiple times on the surface of the film-like master mold. Next, the gold-plated resin particles are wiped with a cloth, so that the gold-plated resin particles are filled in the concave part of the film-like master mold cut at 30 cm in the length direction. Here, since there are unfilled gold-plated resin particles in the resin mold, the number of gold-plated resin particles to be spread or the number of times of spreading are adjusted, so as to obtain an area where the gold-plated resin particles are in a predetermined state of being released.

[0154] <Transfer of gold-plated resin particles to thermally conductive film>

[0155] Next, on the cut film-like master mold filled with gold-plated resin particles under predetermined conditions, the above-mentioned thermal conductive film is aligned and coated so that the length in the longitudinal direction is uniform and the width direction includes the vicinity of the center of the film-like master mold, and pressed at 60°C and 0.5MPa to transfer the metal-coated resin particles. Then, the insulating resin layer film is peeled off from the film-like master mold, and the metal-coated resin particles arranged on the thermal conductive film are pressed (pressing conditions: 60°C to 70°C, 0.5MPa) to press the thermal conductive film, and this is performed at 5 points of the cut film-like master mold, thereby manufacturing a thermal conductive film in which the gold-plated resin particles are buried in an arranged state.

[0156] <Production of laminated body>

[0157] A thermally conductive film in which gold-plated resin particles are embedded between a 30 mm × 30 mm × 2 mm substrate (silicon) and a 30 mm × 30 mm × 2 mm opposing substrate (copper) is arranged so that the gold-plated resin particles are in contact with the substrate, and is heated at 150° C. for 60 minutes and cured to produce a laminate of Example 1.

[0158] (Example 2)

[0159] In Example 1, the same operations as in Example 1 were carried out to produce a laminated body of Example 2, except that the gold-plated resin particles 1 (AUL703 manufactured by Sekisui Chemical Co., Ltd., with a volume average particle size of 3 μm) were replaced with nickel-plated resin particles (Micropearl Ni-plated products manufactured by Sekisui Chemical Co., Ltd., with a volume average particle size of 3 μm).

[0160] (Example 3)

[0161] In Example 1, the gold-plated resin particles 1 (AUL703 manufactured by Sekisui Chemical Co., Ltd., with a volume average particle size of 3 μm) were replaced with gold-plated resin particles 2 (Akko 26GNR series manufactured by Nippon Chemical Industry Co., Ltd., with a volume average particle size of 3 μm). Except for this, the same operations were carried out as in Example 1 to produce a laminated body of Example 3.

[0162] (Example 4)

[0163] In Example 1, the gold-plated resin particles 1 (AUL703 manufactured by Sekisui Chemical Co., Ltd., with a volume average particle size of 3 μm) were replaced with silver-plated resin particles (silver-coated powder series manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd., with a volume average particle size of 3 μm). The same operations were carried out as in Example 1 to produce a laminate of Example 4.

[0164] The cross-sectional SEM photograph of the laminate of Example 4 at the position where the thermal conductive layer and the substrate are in contact is shown in FIG. Figure 3 .Depend on Figure 3 It can be seen that the silver-plated resin particles are arranged at predetermined intervals on the surface of the heat conductive layer in contact with the substrate.

[0165] (Comparative Example 1)

[0166] In Example 1, the gold-plated resin particles (AUL703 manufactured by Sekisui Chemical Co., Ltd., with a volume average particle size of 3 μm) were replaced with resin particles without metal plating (Micropearl SP manufactured by Sekisui Chemical Co., Ltd., with a volume average particle size of 3 μm). Except for this, the same operations as in Example 1 were carried out to produce a laminate of Comparative Example 1.

[0167] (Comparative Example 2)

[0168] A laminated body of Comparative Example 2 was produced in the same manner as in Example 1, except that the transfer of the gold-plated resin particles to the thermal conductive film was not performed.

[0169] (Comparative Example 3)

[0170] In Example 1, a laminate of Comparative Example 3 was produced in the same manner as in Example 1, except that the thermally conductive composition described in Comparative Example 3 described in Table 2 was prepared and a thermally conductive film formed using the thermally conductive composition was used.

[0171] Next, thermal conductivity of each of the obtained laminated bodies was evaluated as follows.

[0172] <Thermal conductivity>

[0173] The thermal resistance (°C·cm) of each obtained laminate was measured according to the method of ASTM-D5470. 2 / W). From the result, the thermal resistance of the substrate and the opposing substrate was subtracted to calculate the thermal resistance of the cured product. From the thermal resistance and the thickness of the cured product, the thermal conductivity (W / m·K) was determined. The thermal conductivity was evaluated according to the following criteria.

[0174] Evaluation Benchmarks

[0175] ◎: Thermal conductivity 20W / m·K or more

[0176] ○: Thermal conductivity is 10W / m·K or more and less than 20W / m·K

[0177] ×: Thermal conductivity is less than 10W / m·K

[0178] [Table 1]

[0179]

[0180] [Table 2]

[0181]

[0182] The details of each component in Tables 1 and 2 are as follows.

[0183] -Curing ingredients-

[0184] *OXBP: 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl manufactured by Ube Industries, Ltd.

[0185] -Curing agent-

[0186] *Polycarboxylic acid: Dexerials Co., Ltd. synthetic product

[0187] -Low melting point metal particles (solder particles)-

[0188] *Sn 42 Bi 58 :Made by Mitsui Mining & Smelting Co., Ltd., volume average particle size Dv: 4μm, melting point 139℃ - Thermally conductive particles -

[0189] * Thermally conductive particles 1: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., volume average particle size Dv: 40 μm

[0190] * Thermally conductive particles 2: Ag particles: manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm - Arranged particles -

[0191] *Gold-plated resin particles 1: AUL703 manufactured by Sekisui Chemical Co., Ltd., volume average particle size 3 μm

[0192] *Gold-plated resin particles 2: manufactured by Nippon Chemical Industry Co., Ltd., 26GNR series, volume average particle size Dv: 3 μm

[0193] *Nickel-plated resin particles: Micropearl Ni-plated product manufactured by Sekisui Chemical Co., Ltd., volume average particle size 3 μm

[0194] * Silver-plated resin particles: Made by Mitsubishi Materials Electronic Chemicals Co., Ltd., silver-coated powder series, volume average particle size 3μm

[0195] * Resin particles without metal plating: Micropearl SP manufactured by Sekisui Chemical Co., Ltd., volume average particle size 3 μm

[0196] -polymer-

[0197] *M1276: Made by Arkema Co., Ltd., polyamide compound

[0198] Industrial Availability

[0199] The laminate of the present invention can achieve high thermal conductivity as a thermal interface material (TIM), and is therefore suitable for use in various electrical device peripherals such as CPUs, MPUs, power transistors, LEDs, and laser diodes, where temperature has an adverse effect on the efficiency and life of component operations.

[0200] This application claims priority based on Japanese Patent Application No. 2022-93012 filed with the Japan Patent Office on June 8, 2022, and cites all the contents described in the above application.

[0201] Explanation of symbols

[0202] 1 Thermal conductive sheet

[0203] 2 Cooling module

[0204] 2a Main side

[0205] 3Heating element (electronic components)

[0206] 3a Top

[0207] 5 Heat sink

[0208] 6 Wiring board

[0209] 7 Laminated body

[0210] 10 Laminated body

[0211] 11. Substrate

[0212] 13. Thermal Conductive Layer

[0213] 14 Opposing substrate

[0214] 15 Metal coated resin particles

[0215] 16 Thermal Conductive Particles

Claims

1. A laminate, characterized in that: have: substrate, and On the substrate, the metal-coated resin particles are arranged in a state of being separated at predetermined intervals, and the heat conductive layer contains a curing component, a curing agent for curing the curing component, heat conductive particles, and low melting point metal particles, The metal-coated resin particles are in contact with the substrate, the volume average particle size of the metal-coated resin particles is smaller than the volume average particle size of the thermally conductive particles, The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, a molding resin, stainless steel, and ceramics.

2. The laminate according to claim 1, The metal-coated resin particles are in contact with a portion of the thermally conductive particles included in the thermally conductive layer.

3. The laminate according to claim 1 or 2, The ratio (A:B) of the volume average particle size A of the metal-coated resin particles to the volume average particle size B of the thermally conductive particles is 1:2 to 1:

20.

4. The laminate according to claim 1 or 2, The volume average particle size of the metal-coated resin particles is 0.3 μm or more and 30 μm or less.

5. The laminate according to claim 1 or 2, The thermally conductive particles have a volume average particle size of 1 μm or more and 100 μm or less.

6. The laminate according to claim 1 or 2, The metal-coated resin particles are at least one selected from the group consisting of gold-plated resin particles, silver-plated resin particles, copper-plated resin particles, and nickel-plated resin particles.

7. The laminate according to claim 1 or 2, The thermally conductive particles are at least any one of copper particles, silver-coated particles, and silver particles.

8. The laminate according to claim 1 or 2, The low-melting-point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In.

9. The laminate according to claim 1 or 2, The curing component is at least one of an oxirane ring compound and an oxetane compound.

10. The laminate according to claim 1 or 2, An opposing substrate is provided on the heat conductive layer and is opposed to the substrate. The opposing substrate includes at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.

11. A method for producing a laminate, characterized in that: The process includes the following steps: A heat conductive layer forming step of forming a heat conductive layer on a substrate, wherein the heat conductive layer includes metal coated resin particles arranged at predetermined intervals and containing a curing component, a curing agent for curing the curing component, heat conductive particles, and low melting point metal particles. The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, a molding resin, stainless steel, and ceramics.

Citation Information

Patent Citations

  • High-heat-conductivity composite

    JP1994196884A

  • Insulating heat-conductive structure, method for manufacturing the same, and substrate for power module

    JP2007214492A

  • Functional particle arrangement sheet and manufacturing method thereof and electrophoresis display medium using the same

    JP2016126843A

  • Adhesive sheet

    JP2017025313A

  • Heat radiation material, method for producing heat radiation material, heat radiation material kit, and heat generator

    US20210332281A1